The Effect of Independent Board of Commissioners and Capital Intensity on Tax Avoidance - Yasmin F., Rahajeng; Meythi, Meythi; Martusa, Riki; Rapina, Rapina (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
The reason of this consider is to look at how the free board of commissioners and capital concentrated have an impact on assess shirking. The data gotten comes from the inspected yearly reports for 2020 to 2022 of coal mining companies recorded on the Indonesia Stock Trade. The number of perceptions chosen utilizing purposive determination is 45 information on the money related explanations of coal mining businesses gotten from the Indonesia Stock Trade and the company's site. The factors watched in this ponder incorporate assess evasion as the subordinate variable, capital escalated and autonomous board of commissioners as free components. The investigate discoveries appear that capital escalated and free board of commissioners both have an impact on assess evasion. The discoveries of this consider bolster the theory created and are reliable with the discoveries of other thinks about that found that the free board of commissioners and capital escalated significantly.